PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DENGAN PENERAPAN MEDIA KARTU PERMAINAN BILANGAN DI SDIT DELI INSANI TANJUNG MORAWA - Dwi Novita Sari; Putri Juwita (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
This study aims to improve the results of learning mathematics of elementary school students SDIT Deli Insani of class V on the subject matter of fractions by using number playing card media. The from of this study is classroom action research conducted in 2 cycles, using number playing cards at SDIT Deli Insani in class V Tanjung Morawa. The subjects of this study were the fifth grade students of SDIT Deli Insani, amounting to 30 students. This action was carried out in April 2018. Methods of collecting data using observation and documentation. The data analysis used is quantitative and qualitative analysis. The results of the study showed an increase in students' ability to understand concepts from the first cycle and second cycle. Percentage of increase in pre-action results, cycle I and cycle II students' concept comprehension ability that is 13.04% for indicators identifying number forms using number game cards (dominoes) and indicators solving problems in fractional form operations using dominoes 27.26%. the success indicator in cycle II reaches 80%. Thus the application of number game cards can improve students' understanding of mathematical concepts at SDIT Deli Insani in Class V.